Friendship as a Mode of Theological Engagement: David Ford's Exploration of Christian Wisdom - Torrance, Iain R. 1949- (2009)
David Ford's Christian Wisdom is offered in the context of navigating between a theology articulated abstractly and a theology engaged with human practicalities. He explores the notion of love of God for God's sake, love of God purged of any desire for benefit, and an understanding what it is to do theology within earshot of the cries of those in distress. These themes are brought into intense dialogue with the teaching of Jesus, the Shoah, and the book of Job. Subsequently, the understanding of Christian wisdom is tested against the inter-faith wisdom disclosed in Scriptural Reasoning, in understanding the formation of Christian wisdom through the evolution and re-invention of universities especially after trauma, and the interpersonal wisdom sought in the communities of L'Arche.